Ballistic performance of Cross-laminated Timber (CLT). (June 2019) - Sanborn, K.; Gentry, T.R.; Koch, Z.; Valkenburg, A.; Conley, C.; Stewart, L.K.
Highlights: Created first-ever public ballistic data set for Cross-laminated Timber. Related the ballistic performance to the species of wood found in the CLT (Spruce Pine Fir – South and Southern Yellow Pine). Developed and calibrated models for predicting the embedment depth as well as residual velocity. Abstract: Cross-laminated Timber (CLT) is a relatively new building material that has gained recent attention in the United States construction industry. CLT is a prefabricated, engineered wood product, composed of three or more plies of lumber with alternating ply directions. CLT is relatively strong and stiff, with the potential to meet the requirements for structures that are subjected to a variety of loading conditions. While CLT's response to static, dynamic (i.e., seismic), and fire loads has been characterized in the past, its response to the loads seen in force protection scenarios (i.e., blast or ballistic) is much less understood. In order to begin to fill this gap in knowledge, one of the first known sets of ballistic experiments were conducted on CLT and the results were used to develop and validate predictive models. This article describes the results of 122 ballistic experiments conducted at the United States Army Engineer Research and Development Center (ERDC). The experiments were conducted on two species of CLT of varying thicknesses: Spruce Pine Fir-South and Southern Yellow Pine. The experiments measured either penetration depth or residual velocity over a range of intermediate striking velocities. The effects of weathering (i.e., moisture content) were also explored on a data set. The results of the experiments were compared to existing United States Unified Facilities Criteria models for predicting the ballistic response of wood. The findings show the deficiencies in utilizing this wood model for CLT and explore alternate models for prediction. In general, it was found that models that incorporate both projectile and CLT target parameters most accurately predict the response. Most importantly, the results reinforce the necessity for re-calibration of models as new parameters are added to the CLT ballistic characterization database.